2023
DOI: 10.1111/aec.13280
|View full text |Cite
|
Sign up to set email alerts
|

Competition and the life table of cladocerans from a tropical shallow lake

Abstract: Laboratory experiments were carried out to investigate the influence of competition for food, with different combinations of species, using life table data. In Experiment 1, the cultivated chlorophycean Desmodesmus spinosus (Chodat) Hegewald, at a low concentration (0.25 mg C L−1), was used to feed the cladocerans Daphnia gessneri Herbst and Diaphanosoma birgei Kořínek; in Experiment 2, the same alga was used in an even lower concentration (0.15 mg C L−1) to feed three species, D. gessneri, D. birgei, and Ceri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…Our results agree with several studies that report a greater sensitivity of juveniles with the increasing body size of the species [2,5,6,41]. In other studies with cladocerans of Lake Monte Alegre, there was already an indication of the greater sensitivity of young D. gessneri regarding limiting food [25], which resulted in lower rates of juvenile growth compared to C. richardi [42]. In addition, the low reproductive rates of D. gessneri fed seston in the present study agree with work by [43], who reported the low growth of this species in the seston of Lake Monte Alegre, although the quantity and quality of edible algae were favorable to cladocerans, particularly in summer.…”
Section: Experiments 1: Competition Between C Richardi and D Gessneri...supporting
confidence: 92%
See 4 more Smart Citations
“…Our results agree with several studies that report a greater sensitivity of juveniles with the increasing body size of the species [2,5,6,41]. In other studies with cladocerans of Lake Monte Alegre, there was already an indication of the greater sensitivity of young D. gessneri regarding limiting food [25], which resulted in lower rates of juvenile growth compared to C. richardi [42]. In addition, the low reproductive rates of D. gessneri fed seston in the present study agree with work by [43], who reported the low growth of this species in the seston of Lake Monte Alegre, although the quantity and quality of edible algae were favorable to cladocerans, particularly in summer.…”
Section: Experiments 1: Competition Between C Richardi and D Gessneri...supporting
confidence: 92%
“…Unlike D. gessneri, the life table parameters of C. richardi were not affected by the competitor. The superiority of C. richardi over D. gessneri agrees with experimental studies with the edible chlorophycean Desmodesmus spinosus [10,25]. The smaller species excluded the larger one in a few days of the experiment at low but not high food concentrations of the edible chlorophycean [10].…”
Section: Experiments 1: Competition Between C Richardi and D Gessneri...supporting
confidence: 83%
See 3 more Smart Citations